Shell-like Structures Non-classical Theories and Applications - Altenbach, Holm; Eremeyev, Victor A. (Advanced Structured Materials, 2011)
In this volume scientists and researchers from industry discuss the new trends in simulation and computing shell-like structures. The focus is put on the following problems: new theories (based on two-dimensional field equations but describing non-classical effects), new constitutive equations (for materials like sandwiches, foams, etc. and which can be combined with the two-dimensional shell equations), complex structures (folded, branching and/or self intersecting shell structures, etc.) and shell-like structures on different scales (for example: nano-tubes) or very thin structures (similar to membranes, but having a compression stiffness). In addition, phase transitions in shells and refined shell thermodynamics are discussed. The chapters of this book are the most exciting contributions presented at the EUROMECH 527 Colloquium "Shell-like structures: Non-classical Theories and Applications" held in Wittenberg, Germany.